Diagnosis of Fibrotic Hypersensitivity Pneumonitis: Is There a Role for Biomarkers? - Pereira, João O. (2023)
Hypersensitivity pneumonitis is a complex interstitial lung syndrome and is associated with significant morbimortality, particularly for fibrotic disease. This condition is characterized by sensitization to a specific antigen, whose early identification is associated with improved outcomes. Biomarkers measure objectively biologic processes and may support clinical decisions. These tools evolved to play a crucial role in the diagnosis and management of a wide range of human diseases. This is not the case, however, with hypersensitivity pneumonitis, where there is still great room for research in the path to find consensual diagnostic biomarkers. Gaps in the current evidence include lack of validation, validation against healthy controls alone, small sampling and heterogeneity in diagnostic and classification criteria. Furthermore, discriminatory accuracy is currently limited by overlapping mechanisms of inflammation, damage and fibrogenesis between ILDs. Still, biomarkers such as BAL lymphocyte counts and specific serum IgGs made their way into clinical guidelines, while others including KL-6, SP-D, YKL-40 and apolipoproteins have shown promising results in leading centers and have potential to translate into daily practice. As research proceeds, it is expected that the emergence of novel categories of biomarkers will offer new and thriving tools that could complement those currently available.